Finance and Development, June 2018. - International Monetary Fund. Communications Department (Washington, D.C. : International Monetary Fund, 2018)
This paper focuses on smart policies that can alleviate the short-term pain of technological disruption and pave the way for long-term gain. As computing power improves dramatically and more and more people around the world participate in the digital economy, care should be taken about how to devise policies that will allow us to fully exploit the digital revolution's benefits while minimizing job dislocation. Digital technology will spread further, and efforts to ignore it or legislate against it will likely fail. Even with short-term dislocations, reorganizing the economy around revolutionary technologies generates huge long-term benefits. The digital revolution should be accepted and improved rather than ignored and repressed. Given the global reach of digital technology, and the risk of a race to the bottom, there is a need for policy cooperation like that of global financial markets and sea and air traffic. The history of earlier general-purpose technologies demonstrates that even with short-term dislocations, reorganizing the economy around revolutionary technologies generates huge long-term benefits.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet